Comparison of steel and fiber-reinforced polymer rebars for mining applications: A numerical approach. (2020) - Mahesh,; Rawat, Prashant; Singh, K.K.; Singh, P.K.
Abstract: Underground mines offer various non-favourable environmental conditions, one among them is the presence of corrosive elements which are not suitable for conventional materials such as steel. This problem can be avoided to a certain extent by using glass reinforced polymer (GRP) rebars. GRP rebars show high tenacity and excellent corrosion resistance compared to conventional steel which extends these materials application to constructions roofing supporting and columns. Thus this paper aims to carry out a comparative study of between steel and GRP rebars strength under tensile, compressive and bending forces using LS-DYNA. Numerical analysis results showed that the stresses generated under tensile and compressive loading are 25% and 37.25% higher for GRP rebars when compared to steel but within the safe limits. Similarly, deformation under tensile and compressive loading for GRP rebar is 62.16% and 87.12% higher compared to steel, respectively. However, load carrying capacity of GRP rebar of GRP rebar is the almost same as steel. Since both the materials showed no sign of damage under 40 kN, thus GRP rebar could be used as a replacement material instead of steel in roof supporting and column in mines.